Sensory Characteristics of Mocaf-Substituted Noodles Enriched with Latoh (Caulerpa lentillifera) - Azkia, Mita Nurul; Wahjuningsih, Sri Budi (Universitas Ahmad Dahlan, 2025)
Noodles are widely consumed globally. However, conventional wheat-based noodles are limited in dietary fiber and functional compounds. Modified cassava flour (mocaf) and latoh (Caulerpa lentillifera) offer potential as natural ingredients to improve the nutritional value and sensory quality of noodles, and Latoh also serves as an alternative to conventional binders such as carboxymethyl cellulose (CMC) and carrageenan. This study aimed to evaluate the sensory characteristics and consumer acceptance of mocaf-based noodles formulated with three different binders: Latoh (MNL), carboxymethyl cellulose (MNCM), and carrageenan (MNCR). The noodles were prepared using a flour blend of 63% mocaf, 36% wheat flour, and 1% binder. Sensory analysis was conducted using a 9-point hedonic scale (taste, aroma, texture, appearance, and overall acceptability) and descriptive analysis. MNCM achieved the highest overall liking score (7.30), with superior ratings in appearance (7.50), taste (6.90), and aftertaste (6.80), indicating better consumer preference due to firmer texture and improved structure. MNCR showed the highest crispness (6.60) but lower fragility (5.00, p<0.05), reflecting brittleness. MNL demonstrated favorable values for fragility (6.80) and mouthfeel (6.10) but received slightly lower taste (5.80) and aftertaste (5.50), likely due to distinct seaweed flavor notes. Principal Component Analysis (PCA) confirmed strong associations of MNCM with elasticity, taste, and overall acceptability, while MNCR aligned with crispness. MNL, although less aligned with hedonic preferences, showed functional potential. In conclusion, CMC was the most effective binder for sensory appeal, while Latoh represents a promising natural alternative that requires further optimization to balance functional benefits with consumer acceptance.